(3eYLe GdSaQs - (3GdSdaj , CMeO Hf eMeO Hf Sdag GdCUHgGfj, UOQ GdOjf CHh WGgQ,J (B576 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG CKfGA UQa (B( (3GdgeRI (B) (3bhdg (B: (3SeYJ CHG GdYHGS CMeO Hf GdMSf GdRQghfi HGdEScfOQjI , jbhd (B: (3QDi GdYJHi ai jhe UGFa s
(3BNQgG (B:s
(3BNQ GdehLhO efgG ef MQa (B( (3dGjGA (B) (3bhdg (B: (3CNHQfG CHh GdbGSe YeQ Hf Gd eDed GdWQShSi bGd jGSjf heeG CfTOfG CHh GdaJM fUQ Hf EHQGgje GdfGHdSi HHjJ GdebOS hde jSe bGFdI s
(3HgG fbU ai GdOGNd hHHYV CWQGagG WeSs
(3ai GdeYgO fSNJGf CNQjGf HQbe (B1234 (3, (B2037 (3JGQjNs
(3Cdag hgh ebje HGdEScfOQjI hPcQ ajg ef hQO Ydjg HgG ef GdTjhN hGdYdeGA ef HdGO eJYOOI hQJHg Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B75s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B185 s
Keywords: (3GdJGQjNs